Dexamethasone and Doxycycline Doped Nanoparticles Increase the Differentiation Potential of Human Bone Marrow Stem Cells - Manuel Toledano-Osorio; Sergio López-García; Raquel Osorio; Manuel Toledano; David García-Bernal; Sonia Sánchez-Bautista; Francisco Javier Rodríguez-Lozano (Pharmaceutics, 2022)
Non-resorbable polymeric nanoparticles (NPs) are proposed as an adjunctive treatment for bone regenerative strategies. The present in vitro investigation aimed to evaluate the effect of the different prototypes of bioactive NPs loaded with zinc (Zn-NPs), doxycycline (Dox-NPs) or dexamethasone (Dex-NPs) on the viability, morphology, migration, adhesion, osteoblastic differentiation, and mineralization potential of human bone marrow stem cells (hBMMSCs). Cell viability, proliferation, and differentiation were assessed using a resaruzin-based assay, cell cycle analysis, cell migration evaluation, cell cytoskeleton staining analysis, Alizarin Red S staining, and expression of the osteogenic-related genes by a real-time quantitative polymerase chain reaction (RT-qPCR). One-Way ANOVA and Tukey’s test were employed. The resazurin assay showed adequate cell viability considering all concentrations and types of NPs at 24, 48, and 72 h of culture. The cell cycle analysis revealed a regular cell cycle profile at 0.1, 1, and 10 µg/mL, whereas 100 µg/mL produced an arrest of cells in the S phase. Cells cultured with 0.1 and 1 µg/mL NP concentrations showed a similar migration capacity to the untreated group. After 21 days, mineralization was increased by all the NPs prototypes. Dox-NPs and Dex-NPs produced a generalized up-regulation of the osteogenic-related genes. Dex-NPs and Dox-NPs exhibited excellent osteogenic potential and promoted hBMMSC differentiation. Future investigations, both in vitro and in vivo, are required to confirm the suitability of these NPs for their clinical application.